ECONOMIC EFFICIENCY OF APPLYING AGILE METHODOLOGIES IN THE PROCESS OF INNOVATIVE IT PRODUCT DEVELOPMENT - Rodionov, Pavlo; Lozovyk, Yurii; Rodionova, Olena (Current Problems of Sustainable Development, 2026)
The article investigates the logical-economic links and financial mechanisms for improving the efficiency of innovative IT product development based on the implementation of agile methodologies. The relevance of the study is driven by a high level of market uncertainty, which increases investment risks and renders traditional waterfall models ineffective. A methodological gap has been identified between the technological advantages of agile methodologies and the financial and economic performance of projects. A conceptual three-stage evaluation model designed as an end-to-end pipeline is proposed, alongside a formalized system of quantitative economic and mathematical indicators that allows for assessing the quantitative impact of resource constraints and engineering metrics on the final financial performance of a project. Special attention is paid to the specifics of managing sunk costs in the IT industry. It is demonstrated that shifting from rigid fixed budgeting to flexible multi-stage discrete financing based on real options theory minimizes capital loss risks. An investment decision tree is constructed to formalize financing trajectories and illustrate the mechanism for exercising the abandonment option in the event of unsatisfactory intermediate iteration results. Furthermore, a management action matrix is substantiated, demonstrating the impact of iterative development on optimizing the total cost of ownership and accelerating cash flows.
Keywords: innovative IT product; agile methodologies; conceptual model; sunk costs; discrete financing; real options